1984
DOI: 10.1111/j.1471-4159.1984.tb02795.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Regulation of Insulin Receptors in Rat Brain

Abstract: An in vitro receptor binding assay, using filtration to separate bound from free [125I]insulin, was developed and used to characterize insulin receptors on membranes isolated from specific areas of rat brain. The kinetic and equilibrium binding properties of central receptors were similar to those of hepatic receptors. The binding profiles in all tissues were complex and were consistent with binding in multiple steps or to multiple sites. Similar binding properties were found among receptors in olfactory tuber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(57 citation statements)
references
References 39 publications
5
52
0
Order By: Relevance
“…Insulin can be transported from plasma into brain through the blood brain barrier, achieving concentrations of about 3 pmol/l in the CNS [30,31]. The existence of insulin receptors [32,33] and GLUT-4, an insulin-sensitive glucose transporter [34,35,36], in the CNS supports the idea that insulin can exert direct actions in the CNS. Pre-incubation with insulin promotes survival of cultured neurons during glucose deprivation by facilitating glial glycogen synthesis [37].…”
Section: Discussionmentioning
confidence: 67%
“…Insulin can be transported from plasma into brain through the blood brain barrier, achieving concentrations of about 3 pmol/l in the CNS [30,31]. The existence of insulin receptors [32,33] and GLUT-4, an insulin-sensitive glucose transporter [34,35,36], in the CNS supports the idea that insulin can exert direct actions in the CNS. Pre-incubation with insulin promotes survival of cultured neurons during glucose deprivation by facilitating glial glycogen synthesis [37].…”
Section: Discussionmentioning
confidence: 67%
“…Functional properties ofthe a-subunit of the insulin receptor, such as the binding kinetic parameters, pH optima, time, and temperature dependence, and specificity of insulin binding, are indistinguishable from the peripheral receptors (1,2,5,7). In contrast, other properties of adult rodent brain receptor, such as its apparent inability to down-regulate after exposure to high insulin concentration (7,8), differ from those of peripheral insulin receptors. The structure ofthe receptor's a-subunit in rat brain differs from that of other tissues: the electrophoretic mobility of the a-subunit covalently labeled with '25I-insulin is consistently more rapid (Mr-115,000 vs.…”
Section: Introductionmentioning
confidence: 80%
“…ID50 range Regulation ofcerebral glial insulin receptors. Studies in the past showed failure of insulin to down-regulate its receptors in rat neuron-enriched cultured brain tissue (7,8). When cells of the cultured human glioblastoma line were preincubated with various concentrations ofinsulin at 370C, and 251I-insulin binding was carried out after extensive washing of the cells, the glial insulin receptors were down-regulated by the ambient insulin concentrations (Fig.…”
Section: Insulin-stimulated Glucose Uptakementioning
confidence: 99%
“…This parallel decrease of insulin and its degrading enzyme IDE in AD raises the possibility that insulin might normally upregulate IDE in the brain via a negative feedback control mechanism to limit the insulin response. Also, unlike peripheral insulin receptors, insulin receptors in the brain are not downregulated by high concentrations of insulin (Boyd and Raizada, 1983;Zahniser et al, 1984), leaving IDE as a plausible effector molecule with upregulation that could turn off insulin signaling in the presence of high insulin levels. Consistent with this hypothesis, a recent report by Ho et al (2004) showed that insulin-resistance caused by a high-fat diet is associated with reduced IDE levels and increased amyloidosis in an AD animal model.…”
Section: Introductionmentioning
confidence: 99%